2011
DOI: 10.1007/s11999-011-1793-2
|View full text |Cite
|
Sign up to set email alerts
|

Ischial Spine Sign Reveals Acetabular Retroversion in Legg-Calvé-Perthes Disease

Abstract: Background Acetabular retroversion has

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…In 2008, Kalberer et al 20 proposed that acetabular retroversion can also be caused by hemipelvic retroversion and not only by the hypoplasia of the posterior wall or the overdevelopment of the anterior wall. Subsequently, some scholars have shown that a high proportion of patients with Perthes disease have a positive ischial spine sign 8 , 21 . This suggests that acetabular retroversion in Perthes disease may be caused by hemipelvic retroversion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2008, Kalberer et al 20 proposed that acetabular retroversion can also be caused by hemipelvic retroversion and not only by the hypoplasia of the posterior wall or the overdevelopment of the anterior wall. Subsequently, some scholars have shown that a high proportion of patients with Perthes disease have a positive ischial spine sign 8 , 21 . This suggests that acetabular retroversion in Perthes disease may be caused by hemipelvic retroversion.…”
Section: Discussionmentioning
confidence: 99%
“…Hemipelvic retroversion may appear as the positive prominence of the ischial spine sign (PRIS). Larson et al 21 researched acetabular retroversion and PRIS in children with Perthes disease and found skeletally immature hips in 90% (37/41) of children with a positive PRIS sign but in only 32% (16/50) of children in the normal control group. Additionally, the positive PRIS sign rate was 90% (9/10) in the early stage of Perthes disease, which showed that acetabular retroversion was probably caused by hemipelvic retroversion in Perthes disease patients.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical compression of the lateral ascending cervical arteries may contribute to the disorder (i.e., in hyperactive patients or activities with repeated abduction), as this region of the trochanteric-neck junction is smaller in children, specifically before the age of eight years. Larson et al described an ischial spine sign that could connote impingement on the vessels at the base of the femoral neck, but chronology of this deformity in the development of LCPD in their series could not be determined [ 6 ]. Furthermore, there is richer vascularity in the anterior femoral neck in black patients than in more susceptible Caucasians [ 20 ], which could explain the relative paucity of reported cases in blacks.…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of LCPD is unknown but is thought to result from vascular congestion and/or coagulation abnormalities in the circulation of the proximal femur [ 2 , 3 ]. The diagnosis has been associated with behavioral disorders [ 4 ], cigarette smoking [ 5 ], femoral and acetabular morphology [ 6 ], genitourinary anomalies [ 7 ], genetics [ 8 ], geography [ 1 ], childhood deprivation [ 9 , 10 ], and high-impact activities such as gymnastics [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…This might be the reason for the high number of dropouts in our study population. Other authors who assessed acetabular retroversion in Perthes’ disease had a similar reduction of radiographs included ( Larson et al 2011 , Kawahara et al 2012 ). To our knowledge, only 1 study so far has assessed the inter-observer agreement of acetabular retroversion using ISS ( Kappe et al 2011 ).…”
Section: Discussionmentioning
confidence: 99%